THE EXCELLENCES OF EXOSKELETONS FOR MEDICAL EQUIPMENT - Arifin, Fatahul; Azharuddin, Azharuddin (AUSTENIT, 2013)
his paper is aimed to inform the advantages of exohand as device that is used in industry and medical treatment on literature review. The  exohand  is manufactured by Festo, Inc. It has many advantages such as design is more comfortable to human or in the other words is ergonomic than the others design. Not only using the latest technology but also consent about the product method alike using selective laser sintering. This model of exoskeletons can be applied in many fields, such as industry and medical treatment for stroke patients.